IDENTIFICATION OF DAMAGE GEAR LANDING SYSTEM OF CESSNA AIRCRAFT - Annga Ardi Anggoro (Institut Teknologi Dirgantara Adisutjipto, 2021)
Designing a system to identify damage based on damage symptom data, so as to get repair handling in accordance with the procedure using a forward chaining expert system, where the expert system is one of the computer systems that aims to solve problems by imitating the human mindset as an expert applied to one of them. Aircraft components that are frequently maintained and damaged are found, namely the landing gear of the Cessna Grand Caravan C208-B aircraft. In the process of making the damage identification system in this final project, the UML (Unified Modeling Language) modeling paradigm and the PHP programming language are used. From the research results, the landing gear damage identification system of the Cessna Grand Caravan C208-B aircraft using a forward chaining expert system can facilitate the search for damage and handling for users or technicians in dealing with a symptom that occurs in the landing gear of the Cessna Grand Caravan C208-B aircraft